A NEW SPECIES OF THE GENUS STRONGYLURIS MULLER 1894, FROM THE GARDEN LIZARD, CALOTES VERSICOLOR (DAUDIN) FROM MANIPUR, INDIA. - LAKSHMIPYARI, W.; GAMBHIR, R.K.; TARNITA, TH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The present paper deals with the description of a new nematode species of the family Heterakidae recovered from the intestine and rectum of garden lizard, Calotes versicolor (Daudin) collected from different localities of Manipur. The present specimens do not agree with any known species of the genus Strongyluris. However, it shows closest resemblance to Strongyluris chamaeleonis Baylis and Daubney, 1922 but differs in many characters like the presence of very fine bristleat the region of cuticular striation. absence of papillae in the head region, longer oesophagus, longer tail, shorter spike, longer spicule, posterior position of the excretory pore.